Pengaruh Kebijakan Dividen Terhadap Kinerja Perusahaan Di Indonesia (Studi Empirik pada Perusahaan-Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesian dengan Probabilistic Regression Model) - Joko Sukendro; C Ambar Pujiharjanto (Conference In Business, Accounting, And Management (CBAM), 2012)
This purpose of this research examines whether dividend policy influences firm performance in Indonesia. The analyses are performed using data derived from the financial statement of listed firms on the IDX during the most recent five-year period. Ordinary Least Squares model is used to estimate the regression equation. In order to operationalise dividend policy ; the study coded: 1 to represent the company has a policy to pay dividend; while: 0 to represent the company has a policy not to pay dividend. The result show negative relationship beetwen return on assets, dividend policy and leverage. The result also reveal are not relationship all independent variables to return on equity and tobin’sq. The main value of this study is the identification of how dividend policy affects performance of firms listed on IDX.Keyword : ROA, ROE, TOBIN’Sq, Dividend Policy, Payout Ratio, Size, Leverage, Growth